Designing animated videos as culinary tourism promotion in Tegal Sawah Village, Karawang City - Ultach Enri; Yuyun Umaidah; Apriade Voutama; Chaerur Rozikin; Richard Julianno Soeganda; Ahmad Ridhoi Fajri; Muhammad Nur Yasin (University of Merdeka Malang, 2022)
Tegal Sawah Village is also famous for its culinary cuisine, namely processed Tutut. By utilizing the scenery of vast rice expanses and various kinds of culinary processing, it makes Karang Taruna Tegal Sawah Village and residents want to make rice field culinary tourism villages to increase the income of residents and also MSMEs in particular. As support for planning, it takes an animated video of rice field tourism planning. The purpose of making animated videos is to help provide the understanding and a design for developing rice field culinary tourism village’s implementation methods by conducting live surveys, place measurements, and animation creation using SketchUp applications. The results of the measure are planned to be 440 m2 road, irrigation canal 243 m2 and rice fields 5307 m2 which will be built more than 15 huts or saung, hydroponic area, parking area, photo booth seats, trash cans, arches, sinks, and various decorations. After the animation is completed then socialization in the village apparatus and the community. Socialization was carried out in front of the Tegal Sawah village apparatus, and the community got a good response and hoped that the video could be realized.